The Hubungan Penerimaan Diri dengan Identitas Diri pada Wanita yang Mengalami Perceraian - Damaiati, Winda Diktriadesta; Nuryani, Reni; Lindasari, Sri Wulan (Jurnal Keperawatan Florence Nightingale, 2024)
Divorce is a life event that triggers psychological changes in the self-acceptance of someone who experiences it, especially women. These negative impacts can affect all aspects of life and can disrupt one's identity. This research aims to determine the relationship between self-acceptance and self-identity in women who have experienced divorce. This type of research is quantitative, with a cross-sectional approach using a correlational design. Sampling used a total sampling technique, totaling 55 respondents. Data were collected using the self-acceptance scale questionnaire and the self-identity questionnaire. The data analysis method used is Spearman's rho correlation statistical test using JASP software. The research results obtained a data value of r = 0.728 with a p-value = 0.001, because the significant value is 0.001 < 0.05, it shows a significant positive relationship between self-acceptance and self-identity. Therefore, the importance of providing psychological and social support shown to increase self-acceptance can have a positive impact on reshaping the self-identity of women who experience divorce.